REKONSEPTUALISASI KEDUDUKAN DAN FUNGSI DPD RI DALAM NEGARA KESATUAN REPUBLIK INDONESIA - Huda, Lalu Halawani; Amnan, Durohim (LPPM Universitas Bina Bangsa, 2023)
The existence of the Regional Representative Council (DPD) in the Indonesian constitutional system does not guarantee a significant role in overseeing the process of running the wheels of the state in accordance with the ideals of independence and the 1998 reforms. The existence of the DPD institution is not accompanied by optimal authority and function to accelerate what becomes duties and main functions (tupoksi). The lack of DPD function is clearly seen in several articles in the 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia). This fact has made the public's perception of the DPD institution very skeptical and considers the DPD to be only an accessory to democracy. Even though this bad opinion was formed because of the lack of duties and functions of the DPD, not because of the quality or the capability of the DPD members themselves. Therefore it is important to propose a proposition to reconceptualize the position and function of the DPD in the Unitary State of the Republic of Indonesia so that the initial aspirations and goals of establishing the DPD can be actualized in state works